Design Of Internal Control System, Accounting Recording, And Financial Reporting Nara Car Rental - Sukiantono Tang; Ristiani Hastuty (ConCEPt - Conference on Community Engagement Project, 2023)
This study reports on the application of an accounting system that has been made to the Nara car rental company. Data processing comes from observations, interviews and written and oral literature. The data is then analyzed to design an accounting-based system on Microsoft Access. The learning stages are carried out virtually through the zoom, whatsapp, power point applications and non-virtual learning is carried out 3 times a month at the company. After carrying out the observation, the researcher will focus on developing an accounting system and internal control at the Nara car rental company. So, when making financial reports the admin does not take a long time to make financial reports. Then, the owner will find it easier to see prospects regarding the state of the company.